Visible and invisible trauma: locating AIDS within a gendered framework in Darrell James Roodt's Yesterday. Issue 4 (1st October 2016) - Tran, Danielle
Abstract: Darrell James Roodt's Academy Award Nominated 2006 movie Yesterday explores how problematic gender dynamics in contemporary South Africa can influence the ways in which the issue of HIV/AIDS is perceived and dealt with socially. The film portrays the complex relationship between HIV/AIDS and identity as one that is both personal and public. Through the dramatization of a couple's experience of living with HIV/AIDS, Roodt's film considers a way in which the epidemic can be structured – through the framework of a gendered narrative. The film's portrayal of Yesterday's journey underlines how this narrative is filled with silences, a fear to disclose, and the blaming and punishment of the female as a scapegoat for HIV/AIDS.